REKONSEPTUALISASI PENYELESAIAN SENGKETA PROSES PENCALONAN PILKADA - Supriyadi, Supriyadi (Jurnal Hukum & Pembangunan, 2021)
This research aims to find the ideal concept of dispute resolution process in the regional head election, so far the practice of election dispute resolution is carried out by two institutions namely Bawaslu and PTTUN. As for the results of this study in the form of the first, philosophically the Bawaslu institution was born from the provisions of Article 22E paragraph (5) of the 1945 Constitution of the Republic of Indonesia which was interpreted to conduct supervision both in the narrow and broad sense (handling violations and dispute resolution) of the holding of elections or the elections. Second, the dualism of institutions that settle local election disputes gives birth to a point of intersection of decisions that do not give birth to legal certainty, a concrete example of the decision on the nomination of the Makassar City elections in 2018. Third, the settlement of nominating dispute processes should ideally be carried out by only one institution namely Bawaslu, and then to ensure justice and legal certainty for the candidate pair can take legal action to correct the decision of the Provincial Bawaslu or Regency/City Bawaslu to the Bawaslu of the Republic of Indonesia.